Rattling Chains Exploring Social Justice in Education - Denti, Louis G.; Whang, Patricia A.; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2012)
Rattling Chains: Exploring Social Justice in Education, is the first book to provide an opportunity to intentionally and deeply grapple with the insights, perceptions, and provocations offered by a rich array of prominent and influential voices in the field of education. The first part of the title, Rattling Chains, signifies the importance of keeping the issue of social justice reverberating in the minds of readers, while also working to unchain thinking from entrenched beliefs and unchallenged assumptions. More specifically, this collection of essays (3z(Bshakes and rattles(3y (Bby providing a variety of vantage points from which to wallow in the complex, tangled, and simultaneously revered and contested notion of social justice. It is hoped that mucking around in the thinking, perspectives, and actions of a variety of educational scholars challenges entrenched beliefs while unearthing provocative insights. Exploring issues of social justice from various standpoints is intended to lead to a more complex understanding of justice that is social, as well as its possibilities, potency, and resultant tensions.s
Keywords: Education; Education; Education (general).